A quasi-experimental study to assess the effectiveness of planned teaching program on knowledge regarding Ayushman Bharat Yojana among community people in Panchayatan village, Greater Noida, Uttar Pradesh - Saikia, Bharati; Pal, Monalisha; Ringkangmai, Wichamjailiu; Krishnan, Suresh (International Journal Of Community Medicine And Public Health, 2023)
Background: The Ayushman Bharat Pradhan Mantri Jan Arogya Yojana (AB-PMJAY) is India’s government-funded health care program that benefits more than 10.74 million poor and vulnerable families. While Pradhan Mantri Jan Arogya Yojana (PMJAY) has helped to correct state imbalances in health care spending, it has not been sufficient to compensate for the inherent fiscal difficulties of poor states. Ayushman Bharat is a holistic need-based health care service which was developed to accomplish the sustainable development goals (SDGS). The purpose of conducting this research is to assess the knowledge regarding Ayushman Bharat Yojana to the people of Panchayatan village, Greater Noida. Methods: A quasi-experimental research design and convenience sampling technique was used to assess the effectiveness of planed teaching program on knowledge regarding Ayushman Bharat Yojana among 59 community people in Panchayatan village Greater Noida. Results: The study found that majority of the samples (64.4%) was between the ages of 16-35 years, (83.1%) were having no previous knowledge and (86.4%) were having no source of information. The findings show mean value of 11.7±4.16 knowledge level regarding Ayushman Bharat Yojana. The post-test mean score was 13.7 which was greater than the pre-test means score 9.6. Results show a significant association between the knowledge scores (post-test) with age (p=0.051) and monthly income (p=0.019). Conclusions: The findings concluded that the planned teaching program on knowledge regarding Ayushman Bharat Yojana among community people in Panchayatan village was effective in increasing the knowledge among community people.